Identifikasi Chaetoceros sp. Secara Molekular dan Uji Antioksidan Karotenoid - Susetyo, M A; Kusumaningrum, H P; Jannah, S N (Berkala Bioteknologi, 2022)
Chaetoceros is one of the largest genus of microalgae that have more than 400 species and it is the primary producers in the marine ecosystem. Chaetoceros sp. have some of the pigment which are very important for their survival include chlorophyll and carotenoid pigments. The purposes of this study are to know the results of Chaetoceros sp. molecular identification using ITS fragments, to know its kinship and to test the ability of the antioxidant activity of pigments carotenoids. The results of ITS fragments identification of Chaetoceros sp. are used to develop the further research, namely to complete morphological information with molecular information intended in the kinship of Chaetoceros sp. Antioxidant test results are used to determine antioxidant activity in Chaetoceros sp. The methods in this research was microalgae isolation of Chaetoceros sp. that used the Doyle method and Doyle, amplification of ITS4 and ITS5 fragments, sequencing analysis and antioxidant activity test. The results of DNA isolation showed a concentration of 2842.1 ng / µl and purity of 1.97. PCR products from amplification of the ITS fragment produced 882 bp. Phylogenetic analysis showed that Chaetoceros sp. has a kinship close to C. muelleri KF 998567.1 and antioxidant activity test showed IC50 values of 72,386 ppm.